FURTHER BIOCHEMICAL AND MORPHOLOGICAL STUDIES OF GRANULE FRACTIONS FROM RABBIT HETEROPHIL LEUKOCYTES - Baggiolini, Marco (The Rockefeller University Press, 1970)
Fractionation of rabbit heterophil leukocyte homogenates by isopycnic centrifugation as well as by zonal sedimentation has helped to characterize further the particulate components of these cells. Four classes have been identified: (A) Large (0.5–0.8 µm) and dense (1.26) azurophil or primary granules, containing all the myeloperoxidase, one-third of the lysozyme, and a major proportion of the lysosomal acid hydrolase activities of the cells. (B) Smaller (0.25–0.40 µm) and less dense (1.23) specific or secondary granules, containing 90% of the alkaline phosphatase and the remainder of the lysozyme activities, but very little if any acid hydrolases. (C) Particles of low density (1.20), containing the remainder of the lysosomal acid hydrolases. This fraction was heterogeneous, but showed abundant small rod- or dumbbell-shaped particles of moderate electron opacity, surrounded by a single membrane (tertiary granules?). The possible origin of these lysosomes from contaminating macrophages could not be ruled out but appeared unlikely. (D) Slowly sedimenting material of very low density (1.14), made up of large, empty vesicular membrane structures, and containing 10% of the alkaline phosphatase, and all of a thiol-dependent acid p-nitrophenyl phosphatase, an enzyme clearly different from the lysosomal acid phosphatase.